Design and development of variable stiffness devices - Ng, Hong Ming (2014)
In robotics, a manipulator is often referred to a device, which is used to control without any direct contact. Variable stiffness manipulators are able to change the stiffness in order to complete different objectives under different conditions. To achieve a variable stiffness manipulator, a device is to be attached along with the driving cable that is always in tension. The main reason is that a standalone cable itself is unable to change the stiffness by tension-pulling manipulating, as the stiffness is actually the tensile strength of the cable’s material. Therefore, a special designed device is needed to introduce variable stiffness. By attaching the VSD along with cable on tension, the equivalent stiffness is the inverse of the sum of the stiffness of VSD and cable. A variable stiffness device (VSD) is proposed to achieve different stiffness profile for different circumstances usage in the industry such as aerospace. The VSD is able to exhibit different stiffness profile just by changing springs of different stiffness. It has the advantages of flexibility for different circumstances usage, easy for assembly, easy for manufacturing and easy for maintenance. Experimental results and detailed calculations analysis have been done to verify the reliability of the variable stiffness device.